Growth and Development in Lady Beetles - Arnold, Shara; Huston, Miranda; Gordon, Haley; Marshall, Jeremy (My University, 2018)
Living in a group can potentially put stress on an animal. This is particularly true for species like Hippodamia convergens, the convergent lady beetle, the larvae of which will cannibalize each other when food sources are limited. This can raise the question of whether or not living in a group affects the growth and development of an individual, and how the growth rate might differ for an individual who is raised alone. This experiment attempts to answer that question by comparing 12 colonies of lady beetles, some of which were reared in groups, some reared alone, and recording the pupation lengths. The hypothesis was that the individuals raised alone would grow and pupate faster than the groups, because they would not have to compete for space or resources. It was ultimately found that while pupation and hatch dates for individual lady beetles were far more variable, there were no large differences in the average length of pupation between groups and individuals.
Keywords: Fall 2018